Advancing Sustainable Mangrove Restoration: A Community-Driven Edu-Ecotourism Business Model in Banyuasin - Puspitaloka, Dyah; Purnomo, Herry; Gasela Majid, Ranti; Dyah Kusumadewi, Sonya; Pebrial Ilham, Qori; Akhfa Hapsari, Farhani; Nadhira, Salwa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Coastal communities in the Banyuasin District heavily rely on mangrove ecosystem services. However, unsustainable livelihood practices are driving mangroves into degradation. Our study aims to identify alternative livelihoods that can transform more sustainable mangrove businesses and practices. This will be achieved by co-developing a business model through participatory action research (PAR) in mangrove villages of Banyuasin. Our study revealed potential community-driven edu-ecotourism businesses in Sungsang and Marga Sungsang Village for further development. This business heavily relies on the natural authenticity of its mangrove, which amplifies the urgency to restore the degraded mangrove in the landscape. Thus, there is a high alignment of the business model canvas components with restoration activities such as the development of a mangrove seedling nursery, selling, and planting. This community-driven business is financially viable, according to the financial metrics, with a net present value (NPV) of IDR 180,148,622, a benefit-cost ratio (BCR) of 1.3, an internal rate of return (IRR) of 52.88%, and a payback period (PBP) of 1.7 years. The development of this business model can leverage sustainable livelihood opportunities and reconcile multiple interests while amplifying the urgency of restoring mangroves. The collaborative efforts among the community during this process serve as an exercise to build collective knowledge, strengthen social ties, and enhance trust and communication. This, in turn, leads to stronger collective action and social capital, which can sustain mangrove restoration beyond the project duration.